FAKTOR RISIKO PREEKLAMPSIA: TINJAUAN ASPEK INTERNAL PADA IBU HAMIL - Hadijah, Hadijah; Putri, Ayu Syah; Asmin, Risna Yunita; Sulistyowati, Endang (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Preeclampsia is a condition characterized by a collection of typical symptoms that appear during pregnancy, childbirth, or the postpartum period. Based on the initial survey, the Kesongo Health Center data showed that there were 17 (11.97%) preeclampia incidents out of 142 pregnant women. The purpose of the study was to determine the relationship of internal aspects in pregnant women to the incidence of preeclampsia. The research design used in this study was cross sectional. The research was conducted at Kesongo Health Center. The research was conducted in June 2024. The study population was all pregnant women in Trimester 2 and Trimester 3 at Kesongo Health Center, Kedungadem District, Bojonegoro Regency in June 2024 as many as 30 people as well as the research sample. The sampling technique used in this study was total sampling. Data analysis was performed univariate and bivariate. The results showed a relationship between the age of pregnant women (p value: 0.000) to the incidence of preeclampsia in pregnant women. It is recommended to the Puskesmas to increase the provision of education to pregnant women about danger signs in pregnancy and healthy lifestyles during pregnancy so that the incidence of preeclampsia can be reduced and maternal mortality can decrease.Keywords: Pregnant Women, Preeclampsia, Age.